Psychrophilic yeasts from Antarctica and European glaciers: description of Glaciozyma gen. nov., Glaciozyma martinii sp. nov. and Glaciozyma watsonii sp. nov. - TURCHETTI, BENEDETTA; BRANDA, EVA; BUZZINI, Pietro; Thomas Hall SR; Connell LB; Theelen B; Müller WH; Boekhout T. (Extremophiles, 2011)
Field campaigns in Antarctica, Greenland and the Italian glaciers aiming to explore the biodiversity of these disappearing environments identified several undescribed yeast strains unable to grow at temperature above 20°C and belonging to unknown species. Fourteen of these strains were selected and grouped based on their morphological and physiological characteristics. Sequences of the D1/D2 and ITS regions of the ribosomal RNA demonstrated that the strains belong to unknown species related to Leucosporidium antarcticum. The new genus Glaciozyma is proposed and two new species are described, namely Glaciozyma martinii sp. nov. and Glaciozyma watsonii sp. nov. Additionally, re-classification of Leucosporidium antarcticum as Glaciozyma antarctica is proposed. Strains of Glaciozyma form a monophyletic clade and a well separated lineage within class Microbotryomycetes (Pucciniomycotina, Basidiomycota). The description of Glaciozyma genus and the re-classification of L. antarcticum reduce the polyphyletic nature of the genus Leucosporidium.